Experiments in Public Management Research 2017
DOI: 10.1017/9781316676912.014
|View full text |Cite
|
Sign up to set email alerts
|

Public Sector Transparency

Abstract: Attention to government transparency has increased greatly in the past 15 years. For instance, US president Barack Obama 1 stated, 'We're not going to change America unless we change the culture that has dominated Washington for far too long. And that means shining a bright light on how Washington works.' Subsequently, the Open Government Directive, which President Barack Obama issued in 2009, has highlighted the importance of transparency for policy makers, politicians, and scholars. Institutional transparenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
1
12
0
5
Order By: Relevance
“…De Fine Licht 2011; Porumbescu 2015; Grimmelikhuijsen et al . 2017). We may need to rethink these more critical lines and more systematically test contextual elements where decision transparency increases trust, and where it does not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…De Fine Licht 2011; Porumbescu 2015; Grimmelikhuijsen et al . 2017). We may need to rethink these more critical lines and more systematically test contextual elements where decision transparency increases trust, and where it does not.…”
Section: Resultsmentioning
confidence: 99%
“…Various experimental studies on the effects of transparency have yielded mixed results at best (Grimmelikhuijsen et al . 2017). For instance, two experimental studies, which looked at the relationship between transparency and legitimacy, found a negative relationship between transparency and legitimacy, especially when the topic that is being made transparent is a contested one (De Fine Licht 2011, 2014; De Fine Licht et al .…”
Section: Regulatory Transparency and Decisionmakingmentioning
confidence: 99%
“…19 Others have investigated the empirical relation between transparency and public values, such as trust and accountability. 20 The debate focuses on whether and to what extent organisations need to adapt to make transparency provisions succeed. Advocates argue for a broad application of transparency and the need for a 'culture shift.'…”
Section: Three Dimensions Of Transparency Policiesmentioning
confidence: 99%
“…Although transparency is often positively associated with performance for a range of different reasons, such as reducing corruption and enhancing financial efficiency and accountability (Hood ; Cucciniello et al ), the pros and cons of transparency are contested and results are mixed (see Hood and Heald ; Fung et al ; Grimmelikhuijsen et al ; de Fine Licht ; Cucciniello et al ; Porumbescu et al ). These mixed results are, however, almost solely based on studies addressing the effects of transparency on citizens (see Grimmelikhuijsen et al ; Grimmelikhuijsen et al ), for example, effects of transparency on citizens' trust in government, their perceived government legitimacy and their voice behaviour (Grimmelikhuijsen et al ). None of these transparency studies, however, are—to the authors' knowledge—based on the perspective and insights of street‐level bureaucrats.…”
Section: Conceptual Framework and Expectationsmentioning
confidence: 99%
“…Transparency research has barely addressed this effect on the relational distance between inspector and inspectee at the street level, nor the implications for inspectors' perceptions of regulatory performance (see Meijer and Homburg ; Grimmelikhuijsen et al ; Porumbescu ). There is, thus, a lack of research on government transparency and regulatory performance in which inspectors' perceptions are put at the centre—even though they are crucial actors in regulatory governance (see de Boer et al ).…”
Section: Introductionmentioning
confidence: 99%